Development of Social Science Textbooks Integrated with Islamic and Local Culture Values - Hardianto Rahman; Andi Fajar Asti; Diarti Angraningsi; Latri Latri; Jamaluddin Jamaluddin; Umar Umar; Ramlan Mahmud (Journal of Educational Science and Technology (EST), 2022)
Social Science textbooks tend to be less dynamic and integrative with Islamic values and local culture. This research is aimed to compose an integrated social science learning textbook which is valid, practical, and effective in improving students’ nationalism character. Type of research and development (R&D) with 4D model procedures (define, design, develop and disseminate) to fulfill the procedure of development. The developed textbook that fulfills scientists’ validity result and its practical use as the participants’ valuation and the implementation of learning. It can enhance students’ nationalism characters and contribute to learning on the character education program, preventive action, enhance the understanding of social, religious, and cultural life values and it should be widely recognized by educators.